Jong Java in The Whirlpool of The Indonesian National Movement - Yusuf Perdana; Sumargono Sumargono (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This article discusses the journey of Indonesian youth organisations, from Tri Koro Dharmo to Jong Java, as part of the Indonesian national movement during the ethical policy period. The research method used is historical research with a literature study approach to reveal how the changes from Tri Koro Dharmo to Jong Java reflect the development of the Indonesian youth movement. Based on the results of the research, it was found that the education provided by the Dutch colonial government, although intended to create a skilled workforce, actually gave rise to educated youth who fought for Indonesia. The youth's dissatisfaction with the dominance of their elders in Budi Utomo led to the establishment of Tri Koro Dharmo in 1915, which was later renamed Jong Java in 1918. This organisation initially focused on Javanese culture but became increasingly inclusive by accepting young people from all over Indonesia. Through congresses and meetings, Jong Java fostered a sense of unity and political awareness among young people. The name change to Jong Java signified a transformation from a limited organisation to a more open one. Jong Java's success peaked with the 1928 Youth Congress, which united various youth organisations in the struggle for Indonesian independence.